2021
DOI: 10.1007/s10853-021-06145-0
|View full text |Cite
|
Sign up to set email alerts
|

Architected poly(lactic acid)/poly(ε-caprolactone)/halloysite nanotube composite scaffolds enabled by 3D printing for biomedical applications

Abstract: Herein, we report the physicochemical, thermal, mechanical and biological characteristics, including bioactivity, biodegradation and cytocompatibility of additive manufacturing-enabled novel nanocomposite scaffolds. The scaffolds comprise a blend of polylactic acid (PLA) and poly-ε-caprolactone (PCL) reinforced with halloysite nanotubes (HNTs). The nanoengineered filaments were developed by melt blending, and the nanocomposite scaffolds were manufactured by fused filament fabrication. Uniform dispersion of HNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Alam et al [ 171 ] reported the mechanical properties of 3D-printed novel nanocomposite scaffolds. The scaffolds consisted of a blend of PLA and PCL reinforced with halloysite nanotubes (HNTs).…”
Section: Pla’s Modificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alam et al [ 171 ] reported the mechanical properties of 3D-printed novel nanocomposite scaffolds. The scaffolds consisted of a blend of PLA and PCL reinforced with halloysite nanotubes (HNTs).…”
Section: Pla’s Modificationsmentioning
confidence: 99%
“…However, that was gradually increased to 4.4% after the addition of 7 wt.% HNTs. Results showed that the mechanical properties, biodegradation rate as well as biological characteristics of the 3D-printed micro architected PLA/PCL/HNT composite scaffolds can be tuned by a suitable combination of PCL and HNTs contents inside the PLA matrix [ 171 ].…”
Section: Pla’s Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For brevity, some selected images are presented in Figure 13 in order to show that fibroblasts adhered in the 3D-printed piece and in the electrospun fibers of the composite. Although we used a commercial 3D-printer filament to print the scaffolds, in all the composites cultured with 3T3 cells we observed cells attached to the main 3D-printed structure (Figure 13A,B), showing the potential of commercial PLA to produce biocompatible materials [62]. The morphology of cells found spread over the surface of 3D-printed pieces of the composite are a blend between some apoptotic cells showing a round shape and a shrunk nucleus, besides a well-formed and interconnected network of fibroblasts linked by polarized filipodia protrusions [63][64][65].…”
Section: T3 Cell Culture In the Presence Of Compositesmentioning
confidence: 96%